Analysis of Different Boundary Conditions on Homogeneous One-Dimensional Heat Equation - M A Q M Sukry; M A H Mohamed; F Jamaluddin; A D H Badrolhisam; N Subani (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology